2022
DOI: 10.3332/ecancer.2022.1490
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly cetuximab in combination with capecitabine and oxaliplatin (XELOX) or irinotecan (XELIRI) in the first-line and second-line treatment of patients with RAS wild-type metastatic colorectal cancer

Abstract: Background: Oral capecitabine in combination with intravenous oxaliplatin (XELOX) or irinotecan (XELIRI) are acceptable substitutions to fully intravenous regimens. Biweekly (as opposed to weekly) cetuximab is more convenient when combined with biweekly chemotherapy. Here, we report the tolerability and efficacy of biweekly cetuximab in combination with biweekly XELOX or XELIRI in patients with RAS wild-type metastatic colorectal cancer (RAS-WT mCRC).Methods: Clinical data of consecutive patients with mCRC who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that biweekly cetuximab in combination with chemotherapy is tolerable and effective, supporting the use of biweekly cetuximab. 15,16 Although not studied extensively, MT with CET against advanced CRC has been suggested. 10,17 Coin-B is a phase-II trial comparing differences between an observation group and CET MT group in patients with mCRC after 12 weeks of chemotherapy combined with CET.…”
mentioning
confidence: 99%
“…Previous studies have shown that biweekly cetuximab in combination with chemotherapy is tolerable and effective, supporting the use of biweekly cetuximab. 15,16 Although not studied extensively, MT with CET against advanced CRC has been suggested. 10,17 Coin-B is a phase-II trial comparing differences between an observation group and CET MT group in patients with mCRC after 12 weeks of chemotherapy combined with CET.…”
mentioning
confidence: 99%